2019
DOI: 10.3390/ijerph16234739
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Benefits of Viewing Nature: A Systematic Review of Indoor Experiments

Abstract: Contact with nature has been proposed as a solution to achieve physiological relaxation and stress recovery, and a number of scientific verification outcomes have been shown. Compared with studies of the other senses, studies investigating the visual effects of nature have been at the forefront of this research field. A variety of physiological indicators adopted for use in indoor experiments have shown the benefits of viewing nature. In this systematic review, we examined current peer-reviewed articles regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(110 citation statements)
references
References 74 publications
(205 reference statements)
6
97
0
7
Order By: Relevance
“…We found a strong relationship between a poor-quality view from the apartment and moderate-severe and severe depressive symptoms. This is consistent with biophilia hypothesis [44], restoration theory [20], and the results of Ulrich's studies in healthcare environments [10], as well as more recent literature reviews [11,29]. Viewing nature may elicit positive emotions, improve attention, reduce stress, and distract from focusing on pain [45,46].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found a strong relationship between a poor-quality view from the apartment and moderate-severe and severe depressive symptoms. This is consistent with biophilia hypothesis [44], restoration theory [20], and the results of Ulrich's studies in healthcare environments [10], as well as more recent literature reviews [11,29]. Viewing nature may elicit positive emotions, improve attention, reduce stress, and distract from focusing on pain [45,46].…”
Section: Discussionsupporting
confidence: 78%
“…Grounding on the latter studies, evidence-based design (EBD) researchers studied the relationship between built environment characteristics and health and organizational outcomes in healthcare facilities, identifying architectural parameters that mostly impact occupants' health or well-being [22][23][24]. Moreover, recent studies highlighted that interacting with natural environments [25,26] or just looking at them [17,[27][28][29] may improve attention and reduce stress, with benefits for mental health and individual well-being. Although in the last few years, the debate around the potential role of the built environment on mental health flourished within the international scientific community, evidence from the literature is still scant, heterogeneous, mainly related to healthcare and working facilities, and frequently based on subjective well-being and small sample sizes [30][31][32].…”
Section: Built Environment and Healthmentioning
confidence: 99%
“…The prominence acquired by the spaces open to the outside is noteworthy, and especially the views of green areas, which, according to Jo et al, bring undoubted psychological benefits, and more positive perceptions [66].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that contact with nature impacts mental health through better stress appraisal, relaxation, and stress recovery [ 7 , 8 ], and improves overall health through boosted immune functioning as well as through other mechanisms, including environmental factors and altered behaviors [ 2 ]. Nature contact behavior is a significant predictor for nature connectedness [ 9 ].…”
Section: Introductionmentioning
confidence: 99%